Penerapan Metode Field Trip untuk Meningkatkan Kemampuan Menulis Puisi pada Siswa Kelas V-B MIN Wonosari Gunungkidul - Muh Widodo (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine the efforts to improve the poetry writing ability of VB graders in MIN Wonosari, Gunungkidul Regency by using the field trip method 2015/2016 academic year. This research is a classroom action research. The subjects of this study were all students of V-B MIN Wonosari Gunungkidul Regency, amounting to 21 students consisting of 8 male students and 13 female students. Classroom action research steps include the activities of planning, implementation, observation, testing, and documentation. The results of the study can be concluded that: (1) the use of field trip methods can improve students' poetry writing skills-average value in the V-B MIN Wonosari class in Kab. Gunungkidul in the pre-cycle was 49.52 with learning completeness 42.86% with sufficient criteria. After carrying out learning with the field trip method increased in the first cycle, the average value became 76.19, with learning completeness of 61.90%, including good criteria. In the second cycle, the average score became 76.72, with 80.95 learning completeness, including very good criteria. (2) There is an increase in the implementation of the learning process and students. From these data, it can be concluded that the application of field trip methods can improve the ability to write poetry in students of V-B MIN Wonosari class, Kab. Gunungkidul.